The role of perceived supervisor support and perceived organisational support on organisational citizenship behaviour in auxiliary police services at a public university: a pilot study - Seman, Mohamad Asri; Ramdan, Mohamad Rohieszan; Salleh, Mad Ithnin; Yee Ong, Sharon Yong; Mohd Fuzi, Nursyazwani; Ngah, Nor Syamaliah (Human Resources Management Academic Research Society (HRMARS), 2024)
Organizational citizenship behavior refers to voluntary actions that are not part of official duties and are not directly rewarded, but can increase the effectiveness of functions in the organization, such as helping colleagues and participating in extra tasks. Although this behavior is often studied in various professions such as teachers and nurses, less attention is paid to auxiliary police officers, especially at universities. Campus auxiliary police officers play a unique role in maintaining security in an increasingly complex campus environment. Therefore, supervisor and organizational support are critical to ensure employee enthusiasm and active participation in the organization. The purpose of this study is to conduct a pilot study regarding the perception of supervisor support, the perception of organizational support, and organizational citizenship behavior in a public college in Malaysia. Content and surface validity analysis of the instrument resulted in several adjustments to the items used. The reliability test of the instrument revealed that all constructs in the study had a high degree of reliability (above 0.70) and excellent internal consistency for each item. The data from the pilot study provide reasonable evidence of the accuracy of the instrument.